Social media, Filipino youth, and political participation an exploration of university students' political actions during the 2016 Philippine elections - Lucas, Jerome Papa 1991 -; Lucas, Jerome Papa 1991 -; Raquiza,Antoinette R. (Quezon City Asian Center, University of the Philippines Diliman, 2019)
"There is much debate on how social media platforms influence political participation. One school of thought points to a strong positive relationship between social media usage and political participation while another argues that there is weak relationship between the two. Still some other scholars assert that the ways in which social media platforms influence political participation differ depending on the domestic context. This study explores this relationship by studying social media usage and political participation among the Philippine university students during the 2016 presidential elections, touted as the country's "first social media elections" due to the millions who reportedly engaged in online politics. The study asks how social media use influences political participation among the country's youth.
The study used quantitative and qualitative research methods to examine the Facebook usage and political participation of fourth year college sutudents of the Polytechnic University of the Philippines (PUP) during the 2016 elections. Findings of a survey of 146 university students suggest the following: one, the majority of Filipino university students who use Facebook for social purposes do so also to read and share political information; two, their online political participation consists mainly of accessing rather than influencing political discussions; and three, offline political participation or involvement in direct political action among young student Facebook users is low, regardless of frequency usage and online political participation. Two focus group discussions were held to better understand the survey findings and provided evidence of the following: one, online political participation among the Filipino university students consisted mainly of gaining information about the candidates; two, reluctance to undertake more pro-active online political participation (e.g. engaging in online political discussions) is due to one or a combination of factors such as low quality of debates, cyber bullying, and misinformation; and three, domestic factors such as family and perceptions of Philippine politics influence offline political participation (including voting). The FGD findings also suggest that the interaction between online and offline political participation may take place in two ways; one, online political participation takes the place of direct political actions (thus, explaining social media users' low offline political participation), and two, online political participation is an extension of users' offline political participation.
This research focused only on a small and specific segment of the Filipino youth population, and thus the findings require further testing. However, this study provides a starting point of more critical examination of the relationship between social media usage and political participation."--Author
Thesis
Keywords: Political participation -- Philippines; Online social networks -- Philippines